2017
DOI: 10.1080/00131911.2017.1358153
|View full text |Cite
|
Sign up to set email alerts
|

Using a “collaborative contextual enquiry” methodology for understanding inclusion for autistic pupils in Palestine

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Stakeholders’ perspectives : Teachers reported that strained relationships between parents and teachers negatively impacted the educational outcomes for students with disability, especially those with autism. The lack of communication at the school led teachers to feel uncomfortable instructing with CWD ( 14 , 47 , 49 , 78 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Stakeholders’ perspectives : Teachers reported that strained relationships between parents and teachers negatively impacted the educational outcomes for students with disability, especially those with autism. The lack of communication at the school led teachers to feel uncomfortable instructing with CWD ( 14 , 47 , 49 , 78 ).…”
Section: Resultsmentioning
confidence: 99%
“…People in the community, for example, regarded CWD from a religious perspective, maintaining that since disabled children were God’s gift, they should be compassionate and empathic toward them. Others refused to recognize CWD as family members ( 49 ). School peers bullied and laughed at CWD, in addition to refusing to interact or build relationships with them ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations